ANALISIS PENGARUH PARAMETER PENGELASAN GTAW PADA STAINLESS STEEL AISI 304 TERHADAP SIFAT MEKANIS DAN STRUKTUR MIKRO - Tumpal Ojahan Rudy; Yusup Hendronursito; Daniel Anggi S (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Abstract: Stainless steel common worn in industry because it has the mechanical properties of a strong, the physical properties of a good, can be recycled without reducing the quality of its constituent compound, decorative and easily cleared, resistant to corrosion, capable of preventing contamination so that the use of stainless steel increase significantly. The use of stainless steel can not be separated from the process of welding, hence writer do research by varying discharge a stream of gas (13,17,21 liter per minute), current (70,130,180 ampere) And types of electrodes (EWLa-1.5, EWTh-2, EWCe-2) With the design Taguchi L9. The purpose of research to know the influence of parameter against the force pull, violence and structure micro, using of GTAW welding with Taguchi methods. The results of tensile test: yield stress dust the highest to parameter stream of gas 17 liters per minutes, the current 70 ampere, electrodes EWLa-1.5 gold with the 387 MPa, maximum stress to the flow of gas 21 liters per minutes, the current 70 ampere, electrodes EWLa-1.5 gold with the 648 MPa and strain to the low of gas 17 liters per minutes, the current 70 ampere, electrodes EWTh-2 red with the 62,2 %. The Rockwell hardness regional of weld to gas flow is 17 liters per minutes, the current 130 ampere, electrodes EWCe-2 grey the hardness poin is 74,2 HRb. Regional HAZ to the gas flow is17 liters per minutes, the current 180 ampere, electrodes EWLa-1.5 gold of 77,3 HRb. Best parameter with the taguchi method to tensile streng of gas flow 21 liter per minutes, the current 70 ampere and types of electrodes EWLa-1.5. Against rockwell hardness test (HRb) found in a stream of gas 17 liter per minutes, the current 130 ampere and types of electrodes EWCe-2.The phase that is formed before welding at micro structure is the phase austenite and the crom, nickel through welding there are adding the phase carbide crom, only the size of the widening weld and haz different.